Research of Grinding Process of Nitriding White Layer on Gear Teeth Surface - Qiu Hongtao; Deng Jiwei; Zhu Fuquan (Jixie chuandong)
For the quality problem of white layer on nitriding teeth surface of turbine oil pump gear,the grinding teeth method and fixture fixing type of hobbing teeth are modified by researching its machining principle and process dimension. A series of optimized plan is proposed and the machining difficulty is solved.